Repeated Three-Hour Maternal Separation Induces Depression-Like Behavior and Affects the Expression of Hippocampal Plasticity-Related Proteins in C57BL/6N Mice. (22nd December 2015) - Bian, Yaoyao; Yang, Lili; Wang, Zhongli; Wang, Qing; Zeng, Li; Xu, Guihua
Abstract : Adverse early life experiences can negatively affect behaviors later in life. Maternal separation (MS) has been extensively investigated in animal models in the adult phase of MS. The study aimed to explore the mechanism by which MS negatively affects C57BL/6N mice, especially the effects caused by MS in the early phase. Early life adversity especially can alter plasticity functions. To determine whether adverse early life experiences induce changes in plasticity in the brain hippocampus, we established an MS paradigm. In this research, the mice were treated with mild (15 min, MS15) or prolonged (180 min, MS180) maternal separation from postnatal day 2 to postnatal day 21. The mice underwent a forced swimming test, a tail suspension test, and an open field test, respectively. Afterward, the mice were sacrificed on postnatal day 31 to determine the effects of MS on early life stages. Results implied that MS induces depression-like behavior and the effects may be mediated partly by interfering with the hippocampal GSK-3 β -CREB signaling pathway and by reducing the levels of some plasticity-related proteins.